Carbon footprint of global cotton production - Zhuhong Yu; Yi Yang (Resources, Environment and Sustainability)
Cotton constitutes one-quarter of the global fiber market. With growing global attention to the carbon footprint and net-zero pathways of the fashion and textile industries, it is essential to quantify the life-cycle greenhouse gas (GHG) emissions, or carbon footprint, of cotton production and develop effective emission reduction strategies. Based on life-cycle assessment, we estimate that global GHG emissions from cotton production in 2020 amounts to approximately 63 Mt CO2e, with substantial regional variability observed. Emissions intensity ranges from 0.3 to 1.4 t CO2e per t of cotton produced, with an average of 0.9 t CO2e per t or 1.9 t CO2e per t of fiber produced. Across the countries evaluated, India has the most GHG emissions and, hence, the largest reduction potential, highlighting the need for prioritized localized strategies in that region. Nitrogen fertilizer is identified as the main driver of cotton’s carbon footprint, due to direct N2O emissions and indirect GHG emissions from production. In some regions, phosphorus (P2O5) fertilizer and diesel use are also important sources of emissions. Scenario analysis indicates that cotton’s carbon footprint can be reduced by ∼37% through improving nitrogen use efficiency and increasing manure application, and an additional ∼12% reduction is possible by powering farm equipment with renewable energy. Our study provides important information for decision makers regarding how to make global cotton production more sustainable and climate friendly.